Risk factors for infant developmental problems Factores de riesgo para problemas de desarrollo infantil Fatores de risco para problemas de desenvolvimento infantil - Margaret Rose Santa Maria-Mengel; Maria Beatriz Martins Linhares (Universidade de São Paulo, 2007)
This descriptive-correlational study aimed to detect risks for child developmental problems in the first four years of age, to identify the protective resources in the familiar environment, and to verify the best predictive variables of the development at risk. The non-clinical sample was composed by 120 children registered in a Family Health Program. The assessment instruments for global development, expressive language and familiar environment were used. The logistic regression analysis indicated that the lower the father's educational level, the higher the risk for developmental problems. Both the history of low nutritional state at six months of age and the psychosocial risk in the family environment increased the chances of having expressive language problems. It is concluded that screening tests of risk for developmental problems and the analysis of the psychosocial factors in the familiar context should be considered as preventive intervention procedure in the Family Health Programs. El estudio descriptivo-correlacional objetiva detectar riesgos para problemas del desarrollo del niño en los cuatro primeros años, identificar recursos protectores en el ambiente familiar, verificar las mejores variables antedichas del desarrollo en riesgo, en una muestra no-clínica de 120 niños registrados en un Programa de Salud de la Familia. Fueron utilizados instrumentos de evaluación del desarrollo global, lenguaje expresivo del niño y ambiente familiar. El análisis de regresión logística indicó que cuanto menor escolaridad del padre, mayor chance de riesgo para problemas de desarrollo. El histórico del estado nutricional debajo de lo normal a los seis meses de edad y el riesgo psicosocial en el ambiente familiar aumentaba la probabilidad de problemas de lenguaje expresivo. Concluyendo, la selección de riesgos para problemas de desarrollo del niño y el análisis de factores psicosociales del contexto familiar deben incluirse como procedimientos de intervención preventiva en programas de Salud de la Familia. Este estudo descritivo-correlacional teve por objetivo detectar riscos para problemas do desenvolvimento da criança nos quatro primeiros anos, identificar recursos protetores no ambiente familiar e verificar as melhores variáveis preditoras do desenvolvimento em risco, em amostra não-clínica composta por 120 crianças cadastradas em um Programa de Saúde da Família. Utilizaram-se instrumentos de avaliação do desenvolvimento global, da linguagem expressiva da criança e do ambiente familiar. A análise de regressão logística indicou que quanto menor a escolaridade do pai, maior a chance de risco para problemas de desenvolvimento. A história do estado nutricional abaixo do normal aos seis meses de idade e o risco psicossocial no ambiente familiar aumentava a probabilidade de problemas de linguagem expressiva. Conclui-se que a triagem de riscos para problemas de desenvolvimento da criança e a análise dos fatores psicossociais do contexto familiar devem ser incluídas como procedimento de intervenção preventiva em Programas de Saúde da Família.